2018
DOI: 10.31661/jbpe.v8i1mar.443
|View full text |Cite
|
Sign up to set email alerts
|

Determining Changes in Electromyography Indices when Measuring Maximum Acceptable Weight of Lift in Iranian Male Students

Abstract: Background:Low back pain caused by work, ranked the second after cardiovascular diseases, are among the most common reasons of patients’ referral to the physicians in Iran. This study aimed to determine the changes in back compressive force when measuring maximum acceptable weight of lift in Iranian male students.Methods:This experimental study was conducted in 2015 on 15 young male students were recruited from Tehran University of Medical Science. Each participant performed 18 different lifting tasks involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Considering the results obtained on the high preva-lence of musculoskeletal disorders, especially low back disorders in women workers, it is necessary to perform risk assessments on manual load lifting tasks with valid methods based on anthropometric information and physiological characteristics. Salehi Sahl Abadi et al (27), in a study in 2018 aimed at determining the changes in electromyographic indicators when measuring the maximum acceptable weight lifting load in Iranian students, concluded that if muscle activity is more than 70% of maximum voluntary muscle contraction. The weights in the SNOOK tables, which are one of the methods for evaluating manual load lifting, should be revised (27).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results obtained on the high preva-lence of musculoskeletal disorders, especially low back disorders in women workers, it is necessary to perform risk assessments on manual load lifting tasks with valid methods based on anthropometric information and physiological characteristics. Salehi Sahl Abadi et al (27), in a study in 2018 aimed at determining the changes in electromyographic indicators when measuring the maximum acceptable weight lifting load in Iranian students, concluded that if muscle activity is more than 70% of maximum voluntary muscle contraction. The weights in the SNOOK tables, which are one of the methods for evaluating manual load lifting, should be revised (27).…”
Section: Discussionmentioning
confidence: 99%
“…6. Based on the use of the existing walker and the redesign of the walker, a decrease in compression value was obtained on the L5S1 where the use of the existing walker provided compression of 3568 N and the use of the redesigned walker provided compression of 1985 N, where the allowable load limit was 3400 N [28]. The posture when using the existing walker and redesign walker is shown in Fig.…”
Section: Fig 4 Walker Redesignmentioning
confidence: 99%
“…[ 1 ] Manual handling is defined as any activity that requires a person to use force to push, pull, lift, lower, carries, or holds an object. [ 2 ] Occupational tasks in the printing industry that are considered ergonomically, include Manually carrying newspaper packages, repetitive movements of upper limb associated with paper cutting machines, cleaning and preparing the printing machine, embedding the papers and maintaining the machines, which usually puts a person in a difficult situation causing musculoskeletal damages. [ 1 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Work-related MSDs (WMSDS) can cause productivity reduction, decrease work quality,[ 10 ] and increase in absenteeism. [ 11 ] Evidence has shown that reducing and preventing musculoskeletal problems is an important global priority. [ 12 ] In assessing MSDs, self-report questionnaires[ 13 ] are used as a tool to collect data, with The Nordic Musculoskeletal Questionnaire (NMQ) as the most known.…”
Section: Introductionmentioning
confidence: 99%